Attitudes and access to lung volume reduction surgery for COPD: a survey by the British Thoracic Society. Issue 1 (1st May 2014) - McNulty, William; Jordan, Simon; Hopkinson, Nicholas S; ,
Abstract : Objective: Lung volume reduction surgery for emphysema leads to improved survival in appropriately selected individuals, and it is therefore recommended in national and international guidelines for this group of patients. Despite this, fewer than 100 patients undergo the procedure each year in the UK. Our objective was to establish whether this reflects concerns about morbidity and mortality or difficulties in the referral pathway. Design and setting: We conducted a survey of members of the British Thoracic Society by email to investigate this in the second half of 2013. The survey included questions about access to investigations, the indications for lung volume reduction surgery (LVRS), whether a multidisciplinary meeting discussed eligibility of patients for LVRS and what the morbidity and mortality associated with the procedure was. Results: There were 65 responses, 82% from respiratory physicians. Roughly half of the respondents were either unsure about the risks of death or prolonged (>30 days) hospital stay involved or significantly over-estimated them. In total, 70% did not have a specific multidisciplinary team to discuss the management of patients with advanced chronic obstructive pulmonary disease (COPD). There was no consensus as to which patients with COPD should undergo a CT scan to evaluate them for possible surgery. Conclusions: Patients with COPD require a systematic and multidisciplinary approach to assessment for LVRS and these survey data suggest that work is needed to deliver this evidence-based therapy in a consistent and comprehensive way across the UK.